Neoliberal etiology and educational failure: A critical exploration. Issue 5 (19th January 2022) - Sharma, Ajay
Abstract: Blaming teachers and schools for perceived or actual educational failures are popular tropes for justifying educational reforms in the United States. Critical educational research implicates neoliberalism in the normalized positioning of teachers and schools as the key suspects in educational failures. This article critiques the etiology of neoliberalism through a critical analysis of the nature of causal relata, causal relations, and the assumed populations in causal claims that attribute educational failure to teachers and schools. It makes the case that though the neoliberal etiology may work well for the neoliberal purposes of accountability and governance of public education and the teaching profession, it does not offer valid causal explanations for the instructional dynamic that contributes to educational failures and successes in the school settings. The article argues that the attribution error of blaming teachers and schools can be avoided by adopting complex causality frameworks for understanding educational failure.